Geomorphology of the Ganges fluvial system in the Himalayan foreland: an update - Sinha, Rajiv (Revista Brasileira de Geomorfologia, 2004)
The Ganges is one of the largest fluvial systems in the world rising from the loftiest Himalaya and draining into the Bay of Bengal. Together with the Brahmaputra, it also constitutes the largest delta in the world before finally meeting the sea. The Ganges system passes through a variety of terrain from the rugged mountains through the flat alluvial plains and the sea margin, and also transects variable climatic zones. As a result, the processes, landforms and stratigraphy are strikingly different in different zones of the system. This paper attempts to provide an update on our understanding of this very large and diverse system. A global effort has been made in the last few decades, and the research has focused on a variety of themes. The mountainous catchments have attracted attention in view of the extent of glaciation and extensive erosional processes. The alluvial plains of the Ganges symbolizes the life line of one of the world's largest population. Consequently, a number of studies have been carried out on the morphology, hydrology including flooding history and sediment transport behaviour of the river system. The alluvial stratigraphy of the large valleys and the interfluves in the plains has provided insight about the sedimentation pattern and response to climate change. The deltaic plain is the final destination of this huge sediment dispersal system before it drains into the sea, and it also records the influence of sea level changes apart from the upstream catchment controls over a period of time.